2013
DOI: 10.2298/bah1302183v
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of paratuberculosis on milk production

Abstract: Paratuberculosis (Johne's disease) is a chronic inflammatory bowel disease, primarily affecting ruminants. The aetiologic agent is Mycobacterium avium subsp. paratuberculosis (MAP). The disease is characterised by persistent diarrhea, weight loss and protein-losing enteropathy. Paratuberculosis can cause significant economic loss in affected herds, as a result of reduced milk yield, increased incidence of mastitis, altered milk constituents, increased somatic cell counts, poor feed conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…However, no clear trends were observed. The decrease in the fat and protein content in seropositive cows observed in herd A in the current study was also observed in studies by Vidić et al [35], Bedenictus et al [17] and Sweeney et al [36]. In contrast, the milk from seropositive cows in studies conducted by Lombard et al [27] and Johnson et al [32] showed higher protein and fat content compared to that from seronegative cows.…”
Section: Discussionsupporting
confidence: 88%
“…However, no clear trends were observed. The decrease in the fat and protein content in seropositive cows observed in herd A in the current study was also observed in studies by Vidić et al [35], Bedenictus et al [17] and Sweeney et al [36]. In contrast, the milk from seropositive cows in studies conducted by Lombard et al [27] and Johnson et al [32] showed higher protein and fat content compared to that from seronegative cows.…”
Section: Discussionsupporting
confidence: 88%
“…Economic losses to dairy industry are significant (Lu et al, 2013a;Hasnova and Pavlik, 2006;Vidić et al, 2013); estimated losses to US dairy industry cost $200-250 million annually (Cho et al, 2012;Ottet et al, 1999). Pillars et al (2009) reported averaged $79/cow/year with a median of $66/cow/year annual losses due to paratuberculosis.…”
Section: Economic Impactmentioning
confidence: 99%
“…Animals with paratuberculosis tend to waste away despite of a healthy appetite. Infections with MAP in caprine herds result in significant economic loss, through slow progressive wasting and the subsequent death of the infected animals (Vidic et al, 2013).…”
Section: Introductionmentioning
confidence: 99%